The new World Trade Organization: Pacemaker for world trade? - Harald Großmann; Georg Koopmann; Axel Michaelowa (Intereconomics, 1994)
The Gatt Uruguay Round was finally brought to a conclusion in April following long-drawn-out negotiations. What changes are contained in the new agreements? How should we rate these changes? How important will the future World Trade Organization (WTO) be?
Keywords: 330; International Trade